Machine learning for spatial environmental data theory, applications and software - Kanevski, Mikhail; Kanevski, Mikhail; Timonin, Vadim; Pozdnoukhov, Alexei (Lausanne, Switzerland : EPFL Press ; Boca Raton, Fla. : Distributed by CRC Press, 2009)
Accompanying CD-RM contains Machine learning office software, MLO guide (pdf) and examples of data.
Learning from geospatial data -- Exploratory spatial data analysis : presentation of data and case studies -- Geostatistics -- Artificial neural networks -- Support vector machines and kernel methods.
Title on accompanying CD-ROM: Machine learning office : software for environmental spatial data analysis, full research version.
At head of title: Environmental engineering.
Includes bibliographical references (p. [347]-371) and index.
All age.
System requirements for accompanying CD-ROM: Windows XP or Vista; CD-ROM drive.
Keywords: Environmental mapping -- Software; Machine learning; Geospatial data; Mappings (Mathematics).; Cartography -- Computer programs; Geographic information systems